Engineered Bacterial Outer Membrane Vesicles Hitchhiking on Neutrophils for Antibody Drug Delivery to Enhance Postoperative Immune Checkpoint Therapy - Meng Guan; Xiao‐Ting Xie; Dong Zhou; Kai Cheng; Bin Zhang; Xin‐Yue Xu; Yong Li; Yi‐Tong Zhou; Wei Peng; Li‐Li Chen; Peng‐Shuo Dong; Si Chen; et al. (Advanced Science)
Abstract In clinical practice, surgical removal of tumors often leaves behind small tumors and circulating tumor cells, increasing the risk of metastasis and recurrence, which seriously affects treatment outcomes. Immunotherapy activates the immune system to monitor and inhibit tumor metastasis and recurrence long‐term. However, inflammatory microenvironments at surgical sites lead to immunosuppressive tumor‐associated macrophages (TAMs), causing immune evasion. Additionally, tumor cells overexpress the immune checkpoint CD47, further weakening the phagocytic and cytotoxic functions of macrophages. Here, the bacterial outer membrane vesicles (OMV) hitchhiking on neutrophils are utilized to precisely deliver immune checkpoint blockade antibodies to the tumor resection site. Escherichia coli is reprogrammed to express CD47 antibody and used to extract CD47 antibody‐containing OMV, followed by insertion of Ce6 photosensitizer into the membrane (OC47‐Ce6). Purified autologous neutrophils phagocytose and carry OC47‐Ce6 for precise targeting to the postoperative tumor resection site, mediating tumor cell killing, aCD47 release, and tumor‐associated antigen presentation by light. In vitro and in vivo experiments demonstrate that OC47‐Ce6 enhances TAM phagocytic function through TAM polarization and CD47 blockade. This approach effectively activates T‐cell anti‐tumor immune responses and significantly reduces the risk of postoperative tumor recurrence and metastasis.